Peran Guru Dalam Mengembangkan Karakter Siswa Kelas V SD Negeri Kabupaten Kecamatan Klaten Tengah Kabupaten Klaten Tahun Pelajaran 2023/2024 - Amalina Mutiara Anindyta; Ronggo Warsito; Putri Zudhah Ferryka (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research uses a descriptive qualitative approach, which is a research method used to research on natural object conditions. Where the researcher is the key instrument. The data validity technique uses source and method triangulation. Data were collected by observation, interview, and documentation. Data analysis through interactive analysis which includes data reduction, data presentation, conclusion drawing or verification. The aim is to know systematically about the research focus, knowing the role of teachers in developing student character and what obstacles are experienced by teachers in developing the character of fifth grade students at SD Negeri Kabupaten. The background of this research problem is based on the author's observations which show several factors that influence the existence of student bad behavior in the role of teachers in developing student character. With this the author intends to examine what problems occur in grade V students of SD Negeri Kabupaten. The conclusion of this research is that the role of the teacher can develop the character of fifth grade students of SD Negeri Kabupaten. The conclusion of this research is evident from the results of previous researchers who have conducted research.